2013
DOI: 10.1371/journal.pgen.1003857
|View full text |Cite
|
Sign up to set email alerts
|

Stimulation of mTORC1 with L-leucine Rescues Defects Associated with Roberts Syndrome

Abstract: Roberts syndrome (RBS) is a human disease characterized by defects in limb and craniofacial development and growth and mental retardation. RBS is caused by mutations in ESCO2, a gene which encodes an acetyltransferase for the cohesin complex. While the essential role of the cohesin complex in chromosome segregation has been well characterized, it plays additional roles in DNA damage repair, chromosome condensation, and gene expression. The developmental phenotypes of Roberts syndrome and other cohesinopathies … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
89
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 67 publications
(100 citation statements)
references
References 113 publications
11
89
0
Order By: Relevance
“…reported in non-neuronal cell culture models of these conditions (71,72). Therefore, the pathological sequel triggered by neuronal ribosome deficiency may underlie the neurological phenotype not only in Rett syndrome but also in cohesinopathies.…”
Section: Table 4 Effects Of Shrnas On Bdnf-induced Dendrite Growthmentioning
confidence: 99%
See 1 more Smart Citation
“…reported in non-neuronal cell culture models of these conditions (71,72). Therefore, the pathological sequel triggered by neuronal ribosome deficiency may underlie the neurological phenotype not only in Rett syndrome but also in cohesinopathies.…”
Section: Table 4 Effects Of Shrnas On Bdnf-induced Dendrite Growthmentioning
confidence: 99%
“…Reduced brain growth and mental retardation are also found in Roberts and Cornelia DeLange syndromes that are caused by deficits in chromatin structure proteins that regulate sister chromatid cohesion (18). As in the case of MeCP2 deficiency, these mutations are proposed to disrupt transcription, including rRNA production (71,72). Indeed, ribosomal deficits were FIGURE 9.…”
Section: Table 4 Effects Of Shrnas On Bdnf-induced Dendrite Growthmentioning
confidence: 99%
“…In vivo studies indicate that rapamycin results in developmental delay in different organisms including Drosophila melanogaster, zebrafish and mice (6,13,14). Previous studies using zebrafish have identified significant effects of rapamycin on autophagy (15), prevention of hepatic steatosis (16), heart development (17) and demonstrated the importance of zebrafish as a mitochondrial and ribosomal disease model (18,19). Although the zebrafish is an emerging model in drug-screening and in vivo disease models (20), evolutionarily conserved effects of rapamycin on the zebrafish transcriptome in addition to the dose-dependency in embryonic/larval size and pigmentation have not previously been studied.…”
Section: Introductionmentioning
confidence: 99%
“…At least for one of such factors, the cohesin SMC1A, deficient rRNA transcription has been proposed as a mechanism that could explain cohesonipathy pathology in non-dividing cells including neurons (74,75). Of note, two other cohesinopathy-associated proteins including NIPBL and SMC3 were also enriched in cerebro-cortical nucleoli, albeit less than 1.3-fold (OMIM #122470 and #610759, supplemental Table S2).…”
Section: Figmentioning
confidence: 99%